National Council of Experts: the place of DPP-4 inhibitors in the treatment of patients with type 2 diabetes mellitus - M. V. Shestakova; G. R. Vagapova; O. K. Vikulova; G. R. Galstyan; T. Yu. Demidova; E. N. Dudinskaya; T. P. Kiseleva; A. M. Mkrtumyan; N. A. Petunina; O. N. Tkacheva; V. V. Fadeev; Y. S. Khalimov; et al. (Сахарный диабет)
TThe annual increase in the prevalence of type 2 diabetes mellitus emphasizes the relevance of the search for new treatment options, along with necessity for regular review of proven therapeutic solutions. Today, dipeptidyl peptidase-4 inhibitors (DPP-4i, gliptins) are effective and safe hypoglycemic therapy, which is included in modern standards of treatment of type 2 diabetes. In 2022, the availability of this group of drugs for Russian patients has significantly increased. This circumstance became a prerequisite for holding a National Council of Experts with the participation of members of the Russian Association of Endocrinologists. The task of the Council was to determine the place of DPP-4i in the treatment of patients with type 2 diabetes in 2023. During the meeting of the Council, experts summarized the evidence base of DPP-4i taking into account the latest scientific data and determined the optimal clinical portraits of patients for the use of DPP-4i in accordance with updated national recommendations.